Modeling a Platform for Distribution of Brazilian Indie Games - Moreira, Alexandre Bezerra; Soares, Liziane Santos (Anais do Workshop de Sistemas de Informação (WSIS); 2024: Anais do XV Workshop de Sistemas de InformaçãoDO - 10.5753/wsis.2024.33694, 2024)
The independent games market in Brazil has grown significantly in recent years, standing out for the creativity and innovation of local developers. However, Brazilian developers still face challenges related to the distribution and promotion of their games, especially on international platforms that do not consider the particularities of the national market. This work proposes the modeling of a platform specifically aimed at Brazilian independent games, offering an environment that meets both the needs of developers and the expectations of players.